Role of chemotherapy for survival in patients with second primary non‐small cell lung cancer - Wang, Zhile (Thorac Cancer, 2020)
BACKGROUND: The therapeutic effect of chemotherapy is still unclear for clinical usage among second primary non‐small cell lung cancer (NSCLC) patients. The aim of this study was to verify the therapeutic effect of chemotherapy and identify the prognostic factors among patients who had received chemotherapy for second primary NSCLC. METHODS: A retrospective cohort was constructed based on the Surveillance, Epidemiology and End Results (SEER) database. Through least absolute shrinkage and selection operator regression, univariate Cox and multivariate Cox regression, we identified the prognostic factors among clinicopathological features. Propensity score matching analysis was used to verify the therapeutic effect of chemotherapy. Survival curves were plotted among the subgroups of the selected factors. We further selected clinicopathological features that would affect the prognosis among patients who had received chemotherapy through a similar process. RESULTS: A total of 769 patients were enrolled to verify the therapeutic value of chemotherapy for second primary lung cancer. Significant differences were observed between the chemotherapy and nonchemotherapy group for cancer‐specific survival. 215 patients who had received chemotherapy were analyzed to identify the factors that might influence outcome on the therapeutic effect of chemotherapy. Age, tumor size, histology and treatment were selected as significant factors. CONCLUSIONS: The therapeutic effect of chemotherapy for second primary NSCLC was found to be significant. Age, tumor size and histology were significant prognostic factors among patients who had received chemotherapy for second primary NSCLC. KEY POINTS: Significant findings of the study: A significant therapeutic effect of chemotherapy for second primary non‐small cell lung cancer was proven through univariate Cox regression and propensity score matching analysis. Prognostic factors for second primary non‐small cell lung cancer patients who had received chemotherapy. What this study adds: Chemotherapy could be applied in clinical practice as an additional therapeutic method for second primary non‐small cell lung cancer patients. We selected prognostic factors for patients who had received chemotherapy to identify patients who were appropriate for chemotherapy.